Terrorism : a critical introduction / Richard Jackson, Lee Jarvis, Jeroen Gunning and Marie Breen-Smyth. - Jackson, Richard, 1967-; Jarvis, Lee, 1979-; Gunning, Jeroen; Smyth, Marie, 1953- (Palgrave Macmillan, 2011)
Terrorism has a long history but the devastating attacks of 9/11 transformed what had been seen as a relatively minor security issue into one of major global significance. This text provides an accessible and balanced assessment of political terror and its study and in the process rethinks many assumptions.